Strategy of National Archives of the Republic of Indonesia (ANRI) in Improving Service Quality: A Case Study of Sub Directorate of Archive Services - Irmalasari, Fitria; Mayesti, Nina (Record and Library Journal, 2017)
This study discuss about the strategy of National Archives on improving the quality of archival services. The main problems of this study are how the strategy of Sub-Directorate of Archives Services on improving the quality services and what the factor that can influence the quality services. This study aimed to describe the servicesâ strategy that is undertook by National Archives of The Republic of Indonesia. This researchâs method is qualitative-descriptive through a case-study approach. The conclusion of this research shows, are: Develop of human resources through the delegation to enroll some education and training, ISO 9001:2008 certification about Management Qualityâs System, integrated static archives servicesâ innovation, usage of technology, synergy of institutions, service of static archiving usage facilitated, and efficiency of archive services timeâs period. The factors that influence the improvement of quality services are human resources, tools and infrastructures, and the availability of the archive.Â